Computing Fifth Geometric-Arithmetic Index for Circumcoronene series of benzenoid Hk - Farahani, Mohammad Reza (JOURNAL OF ADVANCES IN CHEMISTRY, 2007)
Let G=(V; E) be a simple connected graph. The sets of vertices and edges of G are denoted by V=V(G) and E=E (G), respectively. The geometric-arithmetic index is a topological index was introduced by Vukicevic and Furtula in 2009 and defined as Â in which degree of vertex u denoted by dG(u) (or du for short). In 2011, A. Graovac et al defined a new version of GA index as Â where Â The goal of this paper is to compute the fifth geometric-arithmetic index for "Circumcoronene series of benzenoid Hk (kâ‰¥1)".